Acute appendicitis in Montes Claros-MG: a retrospective analysis (Research, Society and Development, 2022)
Acute appendicitis can affect all age groups, being more prevalent in young people, but the worst cases occur in the elderly population. The objective of the present study was to analyze the number of hospitalizations for acute appendicitis in the period from 2015 to 2020. The universe of the SUS Hospital Information System (SIH/SUS) database was the number of hospitalizations for appendicitis in the municipality of Montes Claros-MG, in the mentioned period. The data were obtained from the SIH/SUS, made available by the Department of Informatics of the SUS (DATASUS). A total of 2.196 hospitalizations were recorded, with an annual average of 366 cases. The number of hospitalizations for appendicitis during the analyzed period reduced in recent years (20.5%) and the average mortality rate was low (0.83%). Hospitalizations predominated in males (58.15%), in the 20-29 age group (24.81%) and in patients of mixed race (60.70%). Most cases among patients on an emergency basis (97.95%), with a higher mortality rate (17.6%) and totaled a health expenditure of 1,822,430.99 reais for the public health service. Thus, there is a need to expand health promotion, making people aware of better eating habits and regular intake of dewormers, as appendicitis still causes high health costs in the municipality.